The Contradictions and Depredations of Conservative Neoliberalism. Issue 1 (1st September 2022) - Dorey, Peter
Abstract : In Falling Down, Phil Burton-Cartledge examines how Britain has been subject to decades of neoliberalism since the Thatcher–Major governments (1979–97) in order to transform the British economy (aided and abetted by the New Labour interregnum) and reconstruct civic and social relations, whereby people have been transformed into consumers rather than citizens, and independent economic agents rather than interdependent social actors. Falling Down explains how trade unions have been consistently weakened by economic change, globalization, privatization, repressive legislation, and the dismantling of corporatist policy-making, while workers have been subjected to ever-diminishing job security, reduced autonomy, and stagnant pay, with a concomitant increase in managerial authority, linked to an intensification of the labour process. Yet although he identifies factors which are, or ought to be, undermining its electoral base and political arguments, the Conservative Party might well win the next general election in 2023 or 2024. Thatcherism and neoliberalism may have weakened or destroyed many of the institutions and values that Conservatives have traditionally venerated, but the Conservative Party itself remains stubbornly resilient, and seemingly capable of almost constant reinvention.